(untitled) (diségno, 2024)
The topic of this issue 15 focuses on the theme of landscape representation and is located in an area common to various disciplines in the relationship between nature and culture; it is a complex area, rich in articulations and implications, but structurally permanent, even if historically variable. [read more]